Antimicrobial activity of Enterococcus-derived bacteriocins against multidrug-resistant Pseudomonas aeruginosa: Enterococcus bacteriocin and multidrug-resistant P. aeruginosa - Adul-Hur, Ghufran nazam; Abed, Safa Ahmed Abed; Halah Farazdaq Rafeeq; Mohsin Rasheed Mohsin; Abdul Qader, Esraa Ahmed (Cellular and Molecular Biology, 2025)
Pseudomonas aeruginosa is a key concern in clinical settings due to its high level of resistance to antibiotics, making infections given rise to this bacterium very problematic to treat. The rise of multidrug-resistant bacteria poses a danger to treatments and stresses the necessity to find new antimicrobial drugs. In a neoteric study, P. aeruginosa was found in a suction machine tube, affirming the importance of identifying and managing potential sources of infection in healthcare facilities—many strains of Enterococcus faecium output bacteriocins, which are antimicrobial compounds. The study aimed to produce, isolate, purify, and characterize a new bacteriocin from E. Faecium found in stool samples and to investigate the effects of E. Faecium and its bacteriocin on multidrug-resistant P. aeruginosa in laboratory conditions. E. faecium is a kind of lactic acid bacteria (LAB) set up in the intestines of both humans and animals. In a study, stool specimens from 79 healthy individuals aged 5 to 35 were collected, yielding 70 isolates of Enterococcus spp. These bacteria exhibit growth in aerobic conditions and are identified through the API20 method. A crude preparation was made to extract the E. faecium bacteriocin by combining it with n-butanol in a 1:1 ml ratio in BHIB and then refining it using an ion exchange column. Through this purification process, the final specific activity of purified enterocin GH reached 38.19 U mg with a 4761.9 purification fold. The molecular weight of the E. faecium bacteriocin was determined using ion exchange chromatography. The study also examines how temperature and pH affect the activity of pure enterocin GH using Staphylococcus aureus and P. aeruginosa Type Culture Collection. Both crude and purified enterocin GH from E. faecium exhibited significant antibacterial activity against P. aeruginosa isolates when compared to the control (p<0.05). Additionally, the antibiofilm activity of enterocin GH was found to be more effective than penicillin (p<0.05) in preventing biofilm formation on the suction machine’s tube.